Islamic Educational Values in the Tingkeban Tradition in Melungun Village in Bukit Kemuning District, North Lampung - Nurlinah; Irhamudin; M. Sayyidul Abrori (Journal of Research in Islamic Education, 2026)
This study aims to analyze the process of the Tingkeban Tradition which is still carried out in Melungun Dalam Village, Bukit Kemuning District, North Lampung as a form of gratitude for pregnancy entering its seventh month. This study is based on different views regarding its suitability with Islamic teachings so that it is necessary to study the Islamic educational values ​​contained in it. This study is based on Using Data collection conducted through observation, interviews, and documentation with informants of religious leaders, traditional leaders, pregnant women, and the community. Data analysis is carried out through data reduction, data presentation, and drawing conclusions, while the validity of the data is tested by triangulation of sources and techniques. The results of the study indicate that the Tingkeban tradition contains Islamic educational values ​​in the form of religious, social, and cultural values ​​reflected in joint prayer activities, community togetherness, and the preservation of traditions that do not conflict with Islamic teachings. This tradition also strengthens social relations and fosters gratitude to Allah SWT.